Prototype of a PLA filament extruder - Abd Rashid, Abdul Harith Hazim; Rusli, Ahmad Najmie (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project aims to design, develop and fabricate a low cost prototype of a PLA filament extruder as a proof of concept. The extruder features a horizontal extrusion process and is equipped with a heating element controlled by a temperature controller to ensure consistent melting. A 12V DC motor is used to regulate the extrusion speed providing better control over filament quality. The system is designed to produce filament with a uniform diameter of 1.7mm. The design process involves studying existing models, redesigning using computer-aided design (CAD) software and performing mechanical and electrical fabrication. This project promotes sustainability, reduces filament cost and makes filament recycling accessible for home users. The goal is to produce a compact, affordable and functional filament extruder that supports sustainable practices, reduces filament costs and increases accessibility for personal or small scale use. This prototype could significantly contribute to eco friendly 3D printing and promote responsible material usage within the growing community of 3D printing enthusiasts and professionals.